(untitled) (Research, Society and Development, 2022)
Health education is about the production and systematization of knowledge related to training and professional development to work in the health area. This article aimed to identify how education actions are structured in hospitals for the development and updating of human resources in health. In its methodology, being an integrative review, it brings together findings from studies developed under different methodologies, with a survey of models of education actions aimed at professionals who work in the hospital area, found in the databases PUBMED, LILACS, SCOPUS, Web of Science and CINAHL. Furthermore, the selection of articles brings the result that several initiatives describe education actions aimed at the development of human resources in hospitals. However, it is concluded that despite the various experiences and education programs for the development of human resources in health already implemented, no articles were found that described these actions, highlighting the importance of offering this type of publications.